Mortality and economic expenses of cardiovascular diseases caused by physical inactivity in Spain - Sánchez Oliver, Antonio Jesús (2018)
Fil: Sánchez-Oliver, Antonio Jesús. Seville University. Faculty of Education Sciences. Area of Human Motricity and Sports Performance; España